Generalised fracture mechanics approach to the interfacial failure analysis of a bonded steel-concrete joint - Wouter De Corte; Peter Helincks; Veerle Boel; Jan Klusak; Stanislav Seitl; Geert De Schutter (Fracture and Structural Integrity)
Steel-concrete joints are often made by welded shear studs. However, this connection reduces the fatigue strength, especially in situations where locally concentrated loads occur with a large number of load cycles e.g. in bridge decks. In this paper the shear bond strength between steel and ultrahigh performance concrete (UHPC) without welded mechanical shear connectors is evaluated through push-out tests and a generalized fracture mechanics approach based on analytical and finite element analyses. The connection is achieved by an epoxy adhesive layer gritted with granules. In the tests, specimens made with various manners of preparation of the epoxy interlayer are tested experimentally. Numerical-analytical 2D and 3D modelling of a steel-concrete connection is performed without and with the epoxy interlayer. The model of a bi-material notch with various geometrical and material properties is used to simulate various singular stress concentrators that can be responsible for failure initiation. Thus conditions of crack initiation can be predicted from knowledge of the standard mechanical and fracture-mechanics properties of particular materials. Results of the fracture-mechanics studies are compared with each other and with experimental results. On the basis of the comparison, the 2D simulation of the steel-concrete connection without the epoxy interlayer is shown to be suitable for the estimation of failure conditions.